2017
DOI: 10.14417/ap.1280
|View full text |Cite
|
Sign up to set email alerts
|

Contributos para a auto-regulação do bebé no Paradigma Face-to-Face Still-Face

Abstract: Logo após o nascimento o recém-nascido apresenta comportamentos instintivos de auto-regulação que lhe permitem controlar as suas respostas motoras e vegetativas isolando-se de estímulos perturbadores, organizando-se face ao stress e iniciando ou terminando a interação com os pais. Estes comportamentos evoluem ao longo do primeiro ano de vida. A partir dos 3 meses estes comportamentos parecem organizar-se em estilos comportamentais e ter um peso moderado na qualidade da vinculação mãe-filho(a). No intuito de es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 20 publications
2
13
0
14
Order By: Relevance
“…However, self-comforting behavior decreased substantially in the maternal still-face episode and was very high in the other two episodes. Considering the outcome of these studies and other investigations conducted with Portuguese samples, it was observed that the state self-regulation pattern is significantly more frequent in preterm infants compared to term infants (Fuertes et al, 2014;Seixas, Barbosa, & Fuertes, 2017). The results of this study are original in finding three self-regulation patterns.…”
Section: Palavras-chavesupporting
confidence: 61%
“…However, self-comforting behavior decreased substantially in the maternal still-face episode and was very high in the other two episodes. Considering the outcome of these studies and other investigations conducted with Portuguese samples, it was observed that the state self-regulation pattern is significantly more frequent in preterm infants compared to term infants (Fuertes et al, 2014;Seixas, Barbosa, & Fuertes, 2017). The results of this study are original in finding three self-regulation patterns.…”
Section: Palavras-chavesupporting
confidence: 61%
“…Maternal Intrusiveness Scale (Seixas, Barbosa, & Fuertes, 2017) The Maternal Intrusiveness Scale evaluates the level of intrusiveness the mother exhibited with her infant during the reunion episode of the FFSF. Scores reflect both quantitative (e.g., frequency and duration of intrusive behaviors) and qualitative (e.g., vocal tone, infant response) dimensions of maternal intrusive behavior.…”
mentioning
confidence: 99%
“…Maternal ability to comfort the infant (Seixas et al, 2017) This scale assesses the mother's ability to calm her infant when distressed during the reunion episode of the FFSF paradigm. Scoring assesses the frequency and quality of PREDICTING INFANT REGULATORY PATTERNS maternal comforting behaviors as well as infant behavioral indicators (i.e., rapidity and consistency with which the infant calms down).…”
mentioning
confidence: 99%
“…Psico, Porto Alegre, v. 51, n. 2, p. 1-12, abr.-jun. 2020 | e-34869 Cientes da importância do vínculo para o desenvolvimento infantil, discute-se, a partir de mudanças sociais relacionadas aos papeis familiares, como favorecer a oferta de cuidados para a criança de modo a viabilizar padrões de vinculação como fatores de proteção e autorregulação (Montirosso, Borgatti, Trojan, Zanini, & Tronick, 2010;Seixas, Barbosa, & Fuertes, 2017).…”
Section: /12unclassified